PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP KETEPATAN WAKTU (TIMELINESS) PELAPORAN KEUANGAN (PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018 – 2022) - Nurkholisah, Siti; Sujana, Edy (Vokasi : Jurnal Riset Akuntansi, 2024)
The timeliness of submitting financial reports is an important factor in presenting information as well as reflecting the quality of a company's information. The more timely the information is delivered, the more useful it will be for users of financial reports in making economic decisions. This research aims to determine the effect of profitability, liquidity, leverage, company size and company age on the timeliness of financial reporting. This research was conducted on property and real estate companies listed on the IDX for the 2018 - 2022 period. The sampling technique used purposive sampling with hypothesis testing using logistic regression analysis. The research results show that partially, profitability influences the timeliness of financial reporting of property and real estate companies listed on the IDX. Meanwhile, liquidity, leverage, company size and company age have no effect on the timeliness of company financial reporting on the IDX. Simultaneously, profitability, liquidity, leverage, company size and company age influence the timeliness of company financial reporting on the IDX.